Design, synthesis, in vitro and in vivo evaluation of benzylpiperidine-linked 1, 3-dimethylbenzimidazolinones as cholinesterase inhibitors against Alzheimer's disease. (1st January 2020) - Mo, Jun; Chen, Tingkai; Yang, Hongyu; Guo, Yan; Li, Qi; Qiao, Yuting; Lin, Hongzhi; Feng, Feng; Liu, Wenyuan; Chen, Yao; Liu, Zongliang; Sun, Haopeng
Abstract: Cholinesterase inhibitor plays an important role in the treatment of patients with Alzheimer's disease (AD). Herein, we report the medicinal chemistry efforts leading to a new series of 1, 3-dimethylbenzimidazolinone derivatives. Among the synthesised compounds, 15b and 15j showed submicromolar IC50 values (15b, eeAChE IC50  = 0.39 ± 0.11 µM; 15j, eqBChE IC50  = 0.16 ± 0.04 µM) towards acetylcholinesterase (AChE) and butyrylcholinesterase (BChE). Kinetic and molecular modelling studies revealed that 15b and 15j act in a competitive manner. 15b and 15j showed neuroprotective effect against H2 O2 -induced oxidative damage on PC12 cells. This effect was further supported by their antioxidant activity determined in a DPPH assay in vitro . Morris water maze test confirmed the memory amelioration effect of the two compounds in a scopolamine-induced mouse model. Moreover, the hepatotoxicity of 15b and 15j was lower than tacrine. In summary, these data suggest 15b and 15j are promising multifunctional agents against AD.